Seroprevalence of Hepatitis C, Hepatitis B, and HIV Infections among Hemodialysis Patients in Al-Diwanyah, Iraq - Sayah , Mohammed Abdulkadhim; Abbas , Abbas Ghafil (Medical Science Journal for Advance Research, 2026)
Background: The blood -borne infections such as Hepatitis B (HBV), Hepatitis C (HCV), and Human immunodeficiency virus (HIV) are the most important and significant causes of serious chronic illnesses in patients with end stage of renal disease that undergo long-term hemodialysis sessions. The frequency of hepatitis viral infections amongst hemodialysis patients is relatively elevated and differs among different countries and also among dialysis centers into the same country. Method: During 2024, a cross-sectional study was achieved in Al-Diwanyah province in Iraq, among 275 HD patients from hemodialysis centers of Al-Diwanyah teaching hospital. All positive cases were screened for Hepatitis B surface Ag (HBs-Ag), Hepatitis C virus Ab (HCVAb) and HIV antibody (HIV-Ab), using specific enzyme-linked immunoassay (Elisa technique). Result: The total number of patients attended for receiving hemodialysis services throughout the study period was 275. Only 40/275(14.5%) was positive for hepatitis infections (HBV,HCV or both). Among these, only 7/275(2.5%) patients appeared positive for HBV, 25/275(9%) patients appeared positive for HCV, and 8/275(2.9%) were positive for co-infections of HCV and HBV, while, there was no infection with HIV. Mean of the age of infected patients in present study appeared 39.3 years. The infections were concentrated in males with 29/40(72.5%) more than females 11/40(27.5%). While, infections were concentrated in rural areas with 27/40(67.5%) more than urban areas 13/40(37.5%). Mean of the duration of dialysis courses for positive cases was 3.6 hours and mean of dialysis intervals was three time a week. Conclusion: Adherence to health and preventive standards for kidney dialysis centers to prevent the spread of viral infections among patients is an essential factor in protecting them from the risks of such infections and its long-term complications, which are considered life threatening in the foreseeable future.